2016
DOI: 10.1016/j.wear.2016.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of laser surface melting on erosion–corrosion of X65 steel in liquid–solid jet impingement conditions

Abstract: Laser Surface Melting (LSM) has the potential to increase the resistance of steels to erosion-corrosion. In this study a submerged jet impingement system containing a brine under saturated CO2 conditions with sand has been used to assess the effect of LSM on the erosion-corrosion resistance of X65 steel. Erosion-corrosion rates under different experimental conditions were deduced based on CFD-simulated results and surface profile measurements. Scanning Electron Microscopy (SEM) was used to observe the morpholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…This view is fully proved by Zhao et al [28] . The particle erosion mechanism of CFRP is shown in Figure 4.…”
Section: Mechanismmentioning
confidence: 61%
“…This view is fully proved by Zhao et al [28] . The particle erosion mechanism of CFRP is shown in Figure 4.…”
Section: Mechanismmentioning
confidence: 61%
“…A jet rig system can be employed for both pure erosion under dry sand impingement using an air compressor [57][58][59] and erosion-corrosion under a slurry impingement using a fluid pump [13,[60][61][62][63][64][65][66][67][68]. This section only focuses on the slurry jet impingement systems which are used in the study of erosion-corrosion.…”
Section: Slurry Jet Impingement Rig Systemmentioning
confidence: 99%
“…Consequently, when studying the general performance of the erosion-corrosion under different sand impact angles, it is better to machine the sample smaller than the area of the nozzle to maintain a small deviation of the impact angle on the target surface. However, a sample with a larger diameter of the nozzle can be used to study the local erosion-corrosion behavior at different fluid flow regimes as shown in Figure 5 [61]. Likewise, a series of small samples can be placed at different regions below the slurry jet rig to study the influence of the hydrodynamic parameters on the erosion-corrosion [62,70].…”
Section: Slurry Jet Impingement Rig Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…The surface roughness can improve the friction and wear performance by enabling accumulation of lubricant within the micro-features to provide a secondary supply of lubricant, 28,29 trapping abrasive worn particles to reduce abrasive wear, [30][31][32] and improving the hydrodynamic pressure build up to enhance lubrication. 33,34 Roughness has also been found to affect the transition of lubrication regimes and in some cases the micro-features on the rough surfaces postpone the transition to boundary lubrication. 35 Tomanik et al 36 suggested that the hydrodynamic load support increased by almost 50% to 90% when laser surface texturing was employed.…”
Section: Introductionmentioning
confidence: 99%